Effect of Organic Manures Combinations on Yield Attributes of Finger Millet Var. VL Mandua 379 - , Nabam Akli, Kasinam Doruk, Karge Basar, Sanchung Lida, Anki Mibang, Tadang Meena, Nakeertha Venu (Archives of Current Research International, 2024)
A field experiment was conducted at Himalayan University farm, Itanagar, Arunachal Pradesh, during the kharif season of 2023 with 8 treatments replicated thrice with 24 plots each 3×3 meter in randomized block design, to determine the effect of organic manures on yield of finger millet (Eleusine coracana L.). The experiment included the following treatments T1- Control ,T2- Castor oilcake at 2.5kg/ha+ Poultry manure at 2.5kg/ha,T3- Bone meal at 2.5kg/ha + Poultry manure at 2.5kg/ha,T4- Mustard oilcake at 2.5kg/ha + Goat manure at 2.5kg/ha,T5- Bone meal at 2.5kg/ha + Neem oilcake at 2.5kg/ha + Fym at 2.5kg/ha,T6- Neem oilcake at 2.5kg/ha + Goat manure at 2.5kg/ha, T7- Mustard oilcake at 2.5kg/ha + Poultry manure 2.5kg/ha, and T8- Bone meal at 2.5kg/ha + Goat manure at 2.5kg/ha. All the fertilizers were top dressed on the surface layer of the soil after 1 week of transplantation. The highest finger length (cm) recorded was 6.5 cm at harvest, the highest test weight (g) recorded was 3.1 g at harvest, the highest grain yield recorded was (t ha-1) 4.02 t ha-1 at harvest, highest straw yield (t ha-1) recorded was 7.9 t ha-1 and harvest index (%) 36.78 % at harvest were observed with treatment T5– Bone meal at 2.5kg/ha + Neem oilcake 2.5kg/ha + Fym at 2.5kg/ha.